The Improvement of Learning Outcomes in Reducting Deniminational Fractions is Not the Same as Stad Type Cooperative Learning in Elementary Schools - Nurafni Aswati; Hadiyanto Hadiyanto; Yanti Fitria (International Journal of Educational Dynamics, 2019)
The problem of learning the material geometrical properties particulary rectangular prisms and triangular prisms are: in the learning process, the teacher is not using a variety of methods such as focus group discussions were held infrequently. The results of studying the properties of rectangular and triangular prisms in fifth grade at elementary school with STAD in cycle I and II, which increased the average value obtained in the first cycle an average of 62.04 and the second cycle an average of 81, 04. Of the ability of teachers to design lessons from 75 % to 93%. Activities teachers from 57% to 91% increase. Student activity increased 68.75% from 87.51%. It can be concluded that the STAAD tpess can Abstract Based on the results of observations conducted by researchers in class IV SDI of Bukittinggi Community, it was seen that learning to reduce the disputed fractions was not the same, often dominated by teachers which caused students to be less active. Research procedures include: planning, implementation, observation and reflection. The approach in this study is a qualitative and quantitative approach. Research procedures include: planning, implementation, observation and reflection. The results of the research from each cycle carried out have increased. Seen in: a) Learning cycle I planning 75% while the second cycle 93%. b) Implementation of learning on researchers in cycle I 71% and cycle II 89%. Whereas for the first cycle students 57% and the second cycle 91%. c) Student learning outcomes cognitive aspects of cycle I 68.40 and cycle II 78.40, affective aspects of cycle I 62.04 and cycle II 81.04 and psychomotor aspects of cycle I 70.16 and cycle II 77.0.